Determination Of Total Phenolic, Flavonoid Contents, And Antioxidant Activity Evaluation of Ethanolic Extract From Plumeria Alba - Attasih, Monicia; Muhtadi; Pambudi, Dwi Bagus; Saad, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
A polluted environment and an unhealthy lifestyle can result in an increase in the number of free radicals in the body. This condition can be reduced by consuming antioxidant-rich plants. This study aims to determine the antioxidant activity of the ethanol extract of the Cambodian plant (Plumeria alba L.) and its correlation with phenolic and flavonoid levels. Sample extraction was carried out using the maceration method, antioxidant activity was measured using the DPPH and CUPRAC methods, and total flavonoid and phenolic levels were measured using the spectrophotometer method. The results showed that the ethanol extract of P. alba L stems had inactive antioxidant activity, while the ethanol extract of P. alba L flowers and leaves had weak antioxidant activity with IC50 values of 266.72 ppm and 312.96 ppm. The ethanol extract of P. alba L flowers and leaves has an antioxidant capacity of 208.82 and 207.81 mg trolox equivalent/g extract. The total phenolic content measured from the ethanol extract of P alba L flowers and leaves was 2.28 and 48.43 mg gallic acid equivalent/g extract, while the flavonoid content was 29.73 and 31.26 mg quercetin equivalent/g extract. The antioxidant activity of the extract was positively correlated with phenolic and flavonoid levels.